Safe and effective person- and family-centered care practices during transitions from hospital to home—A web-based Delphi technique - Backman, Chantal; Johnston, Sharon; Oelke, Nelly D.; Kovacs Burns, Katharina; Hughes, Linda; Gifford, Wendy; Lacroix, Jeanie; Forster, Alan J. (Université d'Ottawa | University of Ottawa, 2019)
Research has shown that adverse events during care transitions from hospital to home can have a significant impact on patients' outcomes, leading to readmission, delayed healing or even death. Gaps exist in the ways of monitoring care during transition periods and there is a need to help organizations better implement and monitor safe person-and family-centered care. Value statements are a way to obtain narratives in lay terms about how well care, treatment and support is organized to meet the needs and preferences of patients/families. The purpose of this study was to identify the value statements that are perceived by decision-makers and patients/families to best signify safe person- and family-centered care during transitions from hospital to home.
Keywords: Canada; Decision Making; Female; Humans; Male; Delphi Technique; Hospitals; Internet; Patient Readmission; Patient Transfer; Patient-Centered Care